1985
DOI: 10.1007/bf01893072
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumorous pancreatitis

Abstract: Chronic pancreatitis can occasionally present as a focal, noncalcified mass, indistinguishable from carcinoma. Radiologic studies in 21 such patients were considered to show carcinoma in 16 and an islet cell tumor in 5 patients. Seventeen of the patients came to laparotomy when a palpable mass was found in each; 9 of the patients had a partial pancreatectomy, and multiple biopsy specimens were taken in 8 patients. Four patients did not come to surgery; in them the diagnosis was based on examination of percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…Lammer et al [7] reported that 17 of 21 patients with inflammatory mass underwent surgery because of preoperative radiologic diagnosis of carcinoma or endocrine tumor. Reports on accuracy of EUS in predicting the characterization of pancreatic masses are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Lammer et al [7] reported that 17 of 21 patients with inflammatory mass underwent surgery because of preoperative radiologic diagnosis of carcinoma or endocrine tumor. Reports on accuracy of EUS in predicting the characterization of pancreatic masses are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cases have been reported with chronic rather than acute presentations [7,8] . Some cases in the literature underwent extensive pancreatic surgery for possible carcinoma [7,9] . On the other hand the acute presentation of the patient suggested that the pancreatic head focal lesion was more likely of inflammatory origin.…”
Section: Discussionmentioning
confidence: 99%
“…The malignant transformation of hepatic IPT is extremely rare [7,8] and, to our knowledge, there has only been one case published of primary hepatic lymphoma arising from a hepatic IPT [7]. Tumor-forming pancreatitis has been called an inflammatory pancreatic mass [9] or pseudotumoral pancreatitis [10], and mostly involves the pancreas head with obstructive jaundice [9]. Most recently, a variant of tumor-forming pancreatitis named follicular pancreatitis has been described [11][12][13], histologically differing from autoimmune pancreatitis [11].…”
Section: Introductionmentioning
confidence: 99%